Strategi Pemasaran Digital dalam Meningkatkan Brand Awareness dan Minat Beli pada Fashion Lokal di Indonesia - Nur Hikmah Handayani; Nayra Shiva Salsadila; Wanti Wulandari (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
Digital marketing strategies play a fundamental role in the competitiveness of local Indonesian fashion brands, particularly in building awareness and sparking consumer purchase intention. However, their effectiveness faces complexities, particularly among the Generation Z segment. This study aims to examine the direct influence of digital marketing on purchase intention and compare the effectiveness of cultural narrative-based content strategies (storytelling) with trend-based content (fast-moving). Using narrative and integrative literature review methods across a number of empirical studies, the findings indicate that the influence of digital marketing on purchase intention is not directly significant, but is fully mediated by brand awareness and customer engagement. Trend-based strategies excel at building quick visibility, while cultural narrative-based strategies are more effective in building trust and long-term purchase intention. This study concludes that the success of digital marketing for local fashion depends on the synergy between building brand awareness and customer engagement through content relevant to the brand identity and market context.